2008
DOI: 10.1159/000317146
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Genes Involved with Tick Infestation in <i>Bos taurus</i> and <i>Bos indicus</i>

Abstract: Tick resistant cattle could provide a potentially sustainable and environmentally sound method of controlling cattle ticks. Advances in genomics and the availability of the bovine genome sequence open up opportunities to identify useful and selectable genes controlling cattle tick resistance. Using quantitative real-time PCR and theAffymetrix bovine array platform, differences in gene expression of skin biopsies from tick resistant Bos indicus (Brahman) and tick susceptible Bos taurus (Holstein-Friesian) cattl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…Most of these studies were performed using skin biopsies from the infestation site (Wang et al, 2007;Kongsuwan et al, 2008;Bagnall et al, 2009;Nascimento et al, 2010;Piper et al, 2008Piper et al, , 2010, and thus far, only one study has evaluated the peripheral blood gene expression in bovine (Piper et al, 2009). The lack of available samples before the artificial infestation, however, has limited understanding of the response process to the tick.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these studies were performed using skin biopsies from the infestation site (Wang et al, 2007;Kongsuwan et al, 2008;Bagnall et al, 2009;Nascimento et al, 2010;Piper et al, 2008Piper et al, , 2010, and thus far, only one study has evaluated the peripheral blood gene expression in bovine (Piper et al, 2009). The lack of available samples before the artificial infestation, however, has limited understanding of the response process to the tick.…”
Section: Introductionmentioning
confidence: 99%
“…To investigate if a relationship exists between Ca 2+ signalling and host resistance to cattle tick, we examined mRNA expression of 14 Ca 2+ signalling and Ca 2+ binding protein genes in skin samples taken from cattle with known high (HR) and low (LR) resistance to ticks. The genes selected for this study and their functions are listed in Table 1 and include many signal transducers and regulators of intracellular [Ca 2+ ] (Figure 1) as well as Ca 2+ binding protein genes previously identified to be differentially expressed in the studies comparing B. indicus and B. taurus breeds (3,5). We also included the Ca 2+ dependent cytokine, IL2, in this analysis.…”
Section: Introductionmentioning
confidence: 99%
“…These studies identified many transcriptome changes with significant differentially expressed genes mapped to several biological pathways. Among those genes up-regulated in high resistant hosts were several involved in intracellular Ca 2+ signalling, including EF-hand domains, and Ca 2+ binding protein genes such as sorcin, reticulocalbin and Ca 2+ -calmodulin-dependent kinase (3).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In summary, many molecules have been cited as inhibitors of tick-host homeostasis, but few studies correlate how different bovine phenotypes of infestation acts to neutralize the effect of tick saliva (Carvalho et al, 2008; Kashino et al, 2005; Kongsuwan et al, 2008; Bagnall et al, 2009). Our study of local responses to tick bites involving haemostasis and inflammation and our comparative study of gene expression profiles from ticks fed on susceptible or resistant bovine hosts point both to a bona fide role for the actions of tick anti-haemostatic salivary molecules in vivo and provides information to help explain the mechanisms of resistance against ticks seen in this useful bovine model.…”
Section: Discussionmentioning
confidence: 99%